Analisis Beban Kerja Mental MasinisDengan Metode Rnasa-Tlx(Studi Kasus: PT. KAI DAOP 6 YOGYAKARTA) - Hastuti, Bekti Dwi, Ir. Etika Muslimah, M.M., M.T (2017)
The train is one of the public of transportation in Indonesia, the public transportation as a choice of citizen mobilization that is easy and fast. Machinists have an important role for this public transportation because they are in charge of running at the same time deliver passengers safely and on time without neglecting the services provided. The cause of the crash can be caused by several things which unexpected by a machinist, causing a condition where a high workload but not realized. One of the workload is high, but does not realize is the mental workload, therefore the necessary measurement of mental workload on the driver. This study aims to measure the mental burden machinist from short distance to long distance. The method of this research is the RNASA-TLX method which as a development of NASA-TLX method. This method is devoted to driver-based navigation, where there are six dimensions measured they are mental demands, the demands of visual, auditory demands / hearing, time demands, difficulty driving, and difficulty understanding information. The results of the measurement of mental load on the driver-TLX RNASA score obtained for these short routes of 84.30 and 85.18 for long routes, both classified in the category while the heavy workload of the factors that affect mental load based on the dimensions measured they are visual demands, mental demands, and the demands of the time. On the other side of the results of statistical testing by t-test there was no difference RNASA-TLX score for the short routes and long routes.